Introduction to Systems Biology - Sangdun Choi [ editor ] (Humana Press, 2007)
This book provides an introductory text for undergraduate and graduate students who are interested in comprehensive biological systems .The authors offer a broad overview of the field using key examples and typical approaches to experimental design .The volume begins with an introduction to systems biology and then details experimental omics tools. Other sections introduce the reader to challenging computational approaches to help understand biological dynamic systems .The final sections of the volume provide ideas for theoretical and modeling optimization in systemic biological researchers, presenting most algorithms as implementation, including an up-to-date full range of bioinformatic programs and available successful applications. Informative and cutting -edge, this volume presents a clear and intuitive illustration of the biological systemic approaches and introduces ideal computational methods for research. The book is an indispensable resource, providing a first glimpse into the state-of-the-art in systems biology.